SOSIALISASI PEMBUATAN FILTER AIR SEDERHANA BERBASIS MEDIA ALAM UNTUK MENURUNKAN KADAR CD DAN ZN TERHADAP MAHASISWA JURUSAN KIMIA - Christin Angeline Laia; Delima Sianturi; Kristian Turnip; Nazwa Ramadhani; Ririn Denita Sinaga; Wiranda Hasibuan; Iis Siti Jahro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This outreach activity aimed to enhance Chemistry students’ understanding of heavy metal contamination (Cd and Zn) and the use of simple natural-based filtration as a practical solution for reducing metal levels in water. The program included material delivery, filter demonstration, hands-on practice, and performance evaluation. The filter—composed of cotton, sand, gravel, activated carbon, and zeolite—operated through physical screening, adsorption, and ion-exchange mechanisms. Results showed that students successfully built the filter, understood the scientific processes involved, and observed reduced turbidity and a potential decrease in Cd and Zn. The activity provided educational benefits, improved environmental literacy, and strengthened practical skills in low-cost water treatment technology.